Control Orang Tua pada Anak Usia Dini dalam Kecanduan Game Online - Febi maharani (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of digital technology has made online games an inseparable part of children's lives. However, excessive use of online games can lead to addiction, which can have a negative impact on early childhood development. This research aims to determine appropriate controls in dealing with the negative impact of online games on early childhood development. The research method used is a literature study that analyzes various previous studies related to this topic. Having effective parental supervision, such as limiting play time, choosing appropriate types of play, and providing alternative, more productive activities, can be an important preventive measure. Apart from that, this research also discusses the factors and forms of behavior of children who are addicted to online games. This research concludes that online game addiction can disrupt the learning process, hinder social development, and cause physical health problems such as obesity and sleep disorders